Pendampingan Dan Pelatihan Pencatatan Keuangan Sederhana Berbasis Aplikasi Digital Umkm Kabupaten Klaten - Shika Endarti; Yudas Tadius Andi Candra (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This study aims to assist Herbal Umi and Jakumen, two herbal beverage MSMEs in Klaten Regency, in adopting simple digital financial recording. Prior to the program, both businesses relied on inconsistent handwritten notes or kept no financial records at all. The mentoring method combined direct practice (learning by doing) with contextual analogies, implemented through five structured sessions covering interviews, training, mentoring, and evaluation using the BukuWarung application. The results showed an improvement in both owners' understanding and skills: Herbal Umi is now able to issue digital sales receipts, manage stock, and monitor receivables, while Jakumen, which previously had no records at all, successfully prepared a simple profit-and-loss statement independently for the first time. The main barriers encountered, namely limited digital literacy, difficulty in categorizing transactions, and limited time, were addressed through a gradual, repetitive, and analogy-based approach.